Heat transfer analysis in constructal designed microchannels with perforated micro fins (2023)
This paper documents 3-D numerical optimisation of combined microchannel heat sink with solid and perforated rectangular fins. Constructal design technique is deployed to construct a geometry with reduced material substrate and the effect on the heat transfer is examined. The goal of the study is to minimise the peak temperature or maximise global thermal performance. The axial length and volume of the microchannel are fixed, while the width is allowed to morph. The microelectronic device placed at the bottom of the combined heat sink emits heat flux q″ and the heat deposited at the bottom is removed using a single-phase fluid (water) of Reynolds number Re w in a forced convection laminar regime. The computational domain is descretised and the mathematical equations that govern the fluid flow and heat transfer are solved using the CFD code. Three unique cases were considered in this study. The influence of design parameters (channel width, external shape, and velocity of fluid applied) on the performance of the combined microchannel heat sink is discussed. The study revealed that the solid material substrates used in the manufacturing of the combined microchannel heat sink can be reduced without necessarily compromising the heat transfer at certain applied Re w . The global thermal conductance of the combined microchannel with no perforation on fins increases by 1.1% higher than the microchannel with 1-rectangular perforation on fins and 0.8% above the heat sink with 2-rectangular perforations on fins. The numerical results validation agrees with what is in the open literature.